Preparing for Leadership Turnover in Christian Higher Education: Best Practices in Succession Planning. Issue 1 (1st January 2019) - Barton, Andrew
Abstract: In the face of unprecedented disruption and complexity, the higher education sector appears to be largely underprepared for the projected exodus of senior-level administrators due to retirements and briefer tenures in leadership roles. Given that religiously affiliated institutions account for more than one in five colleges and universities in the United States, it is concerning that relatively few studies have addressed succession planning in this sector, and in Christ-centered higher education in particular. This article provides a review of the literature that has addressed the topic of succession planning and discusses the findings from a single-institution ethnographic case study that explored the culture of succession planning and leader development at Lipscomb University in Nashville, Tennessee. The conceptual framework used in this study was developed through the dissertation research of C. L. Richards in 2009, and is referred to as the 5Cs Model: Strategies for Succession Planning in the Academy . Through a grounded theory study, Richards suggested five strategies leaders should consider as they approach succession planning in academic institutions: culture, champions, communication, competency-based, and continuous . The article then discusses succession planning as an effective process that presidents, boards, and senior leaders can use to intentionally develop a cadre of future leaders, highlighting the unique challenges and best practice opportunities of pursuing this strategy, and recommends several implications for practice in Christian higher education.